Short- and long-term results of organ-sparing surgery in patients with severe diffuse adenomyosis at perimenopausal transition - V. B. Tskhay; G. T. Mikailly; I. I. Tskhay (Фундаментальная и клиническая медицина)
Aim. To study the short- and long-term results of organ-sparing surgery in patients with severe diffuse adenomyosis who are in the perimenopausal age.Materials and Methods. The study included 18 patients with severe diffuse adenomyosis who underwent fertility-sparing excision of diffuse adenomyosis by means of Osada procedure. Efficiency of surgical treatment and subsequent drug therapy was evaluated at 12 and 24 months of follow-up by pelvic ultrasound examination. The frequency of adenomyosis symptoms and quality of life were assessed using the standard SF-36 questionnaire.Results. Recovery of the menstrual cycle, freedom from pain and anemia, and improved quality of life were documented in all cases (18/18), whereas onset of menopause occurred in half of the cases (9/18). In particular, all scales of the Physical Component Summary from SF-36 questionnaire were significantly improved at both follow-up time points.Conclusion. Organ-sparing excision of diffuse adenomyosis using Osada procedure is the option of choice and might represent an alternative to hysterectomy in women with perimenopausal age, in addition to those of earlier reproductive age.